Mergers, acquisitions, and strategic alliances : understanding the process - Gomes, Emanuel (Houndmills, Basingstoke, Hampshire ; New York, NY : Palgrave Macmillan, 2011)
"This book tackles the strategic, financial and procedural aspects of planning and executing mergers, acquisitions and strategic alliances. It also explores the similarities and differences between these various types of transaction and illustrates each with case studies, to help students from final year undergraduate to MBA. "--
Machine generated contents note: -- M&A and Strategic Alliances: The Basic Concepts -- Economic Arguments and Consequences -- Understanding the Processes: Pre-Agreement Issues -- The Evaluation Process: Selecting the type of Arrangement -- Choosing the Right Partner -- Executing the Transaction -- Integration Management.
Includes bibliographical references and index.
Keywords: Consolidation and merger of corporations; Strategic alliances (Business); BUSINESS & ECONOMICS / Mergers & Acquisitions; BUSINESS & ECONOMICS / Strategic Planning; BUSINESS & ECONOMICS / Management